Система моніторингу вартості нумізматичних цінностей - Басюк, Тарас; Дюганчук, Святослав (Видавництво Львівської політехніки, 2014)
In this paper we consider the features of monitoring numismatic values. The main criteria applicable to the Software and this class is based contextual graph displays the projected system as a single process from the main stream input / output.
Keywords: нумізматика; система прогнозування; ціна; монета